AN IDENTIFICATION OF PHRASAL VERB IN MOVIE ENTITLED â€œBEGIN AGAINâ€ - Mahendra, I.G.A.Y.; Ramendra, I.D.P; Agustini, D.A.E. (Language and Education Journal Undiksha, 2018)
This study aimed at: 1) describing the types of phrasal verbs used in movie entitled â€œBegin Againâ€. 2) meaning of phrasal verbs by using syntax used in movie. This study was descriptive qualitative research mainly focused on discovery rather than using statistical analysis. This study used phrasal verb in movie as the object. This study used researcher as main instrument and dictionary to help researcher in collecting the data. This study showed total usage of phrasal verbs in movie. There are 42 Transitive (22 separable, 20 inseparable), 65 Intransitive. Teachers teach about phrasal verb easier and entertaining because object was easier to understand and avoid boredom in learning. Students directly know when they use phrasal verb. Students can be help them to know about phrasal verb and learn something by watching movie which is good for their behaviour. For other researcher can be an additional resource to make similar study.